Breast self-examination practices in nigerian women attending a tertiary out-patient clinic (2015)
BACKGROUND: The morbidity and mortality caused by breast cancer can be decreased by early detection with breast self‑examination (BSE).The objective of this study was to determine the prevalence and the factors determining the practice of BSE. MATERIALS AND METHODS: The study was conducted on 140 women aged above 18 years who presented consecutively in a General Outpatient’s clinic in a tertiary hospital in Nigeria. This was the baseline study from an intervention study which looked at the effect of demonstration of BSE on improving Clinical Breast Examination (CBE) among two groups of respondents. Structured questionnaires were validated and administered by an interviewer and the data were analyzed using Statistical Package for Social Sciences (SPSS) version 12. RESULTS: The overall self-reported prevalence of BSE practice was 62.1% among the respondents. Older women (16, 76.2%), married women (63, 65.6%) and women with tertiary education (51, 68.9%) had the highest prevalence of BSE practice. Prevalence rate was highest for civil servant (25, 78.1%), P = 0.04. The practice of BSE was higher among women with a previous history of breast disease (15, 68.2%) and in respondents with a family history of breast disease (7, 63.6%), Only 11 (12.6%) performed BSE as per guidelines, which was once in a month. CONCLUSION: The prevalence of BSE was found to be high, especially in those with tertiary education and in those with a past personal or family history of breast disease. In resource‑constrained countries, BSE is a screening tool that can be employed to help reduce the breast cancer burden because routine mammography screening is not yet feasible. Women need to be informed about the when and how to perform BSE